Partial correction of cystinuria type A in mice via kidney-targeted transposon delivery - Lauren E. Woodard; Richard C. Welch; Anna Menshikh; Wentian Luo; Felisha M. Williams; Jennifer L. Peek; Feng Sha; Ruth Ann Veach; Aparna Kaja; Thomas M. Beckerman; Talat Alp Ikizler; Matthew H. Wilson (Molecular Therapy: Nucleic Acids)
We used kidney-targeted, non-viral, transposon-mediated gene delivery to express the mouse Slc3a1 transgene in one kidney of cystinuria type A (Slc3a1−/−) mice. We found a 44% reduction in urinary cystine concentration at 154 days post-gene transfer, although there was no significant effect on cystine stone formation. Our results indicate that it is possible to achieve kidney-targeted gene transfer, resulting in reduction of cystine concentration in the urine of a cystinuria type A animal model. This proof of concept lays the foundation for future studies directed at gene therapy for cystinuria and other kidney diseases.